الزمن في الشعر الإماراتي الحديث: دراسة وصفية سيميائية - خنجري، إسحاق بن محفوظ بن خلفان (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study aims to highlight the theme of time in the Modern Poetry of the United Arab Emirates in an interpretive semiotic vision which seeks to trace the signs of time presence in the poetic text through the central theme that has been involved and its relation to the structure of the text and outer space.The study has been applied to five collections of poems.The first namely: Gollous Al sabah Allaa Al Bahar (The poet Ahmed Rashid Thani).The second namely: Gamaly fey Al sour (The poet Mayson Sagger) The third namely: Esme Al Radda Waladi (The poet Habeeb Al saiq).The fourth namely Saker Al waqt (The poet Ibrahim Mohammed Ibrahim). The fifth namely Abbad min Adam (The poet Ahmed Mansoor).The study showed several results, including: time is not a descriptive structure that has a specific form, therefore there are many visions about its structure in existence and divergent signs.Here, the importance of time is expressed through the methodology of description and semantic analysis which expands the interpretive domain of real and visionary time and, thus dual realtionship between truth and dream emerged, a sign of the intensification of sensory intuitive and time .Also, the study showed the dialectic of life and death and its relation to time, where it described the harmony and the differences of time between the dimensions of the soul and the body.